(untitled) - Stein, Jay H. (St. Louis, 1998)
INTERNAL MEDICINE is organized by clinical subspecialty, each divided into three primary sections: an introductory section on the basic principles of a given organ system; a section on laboratory tests, including a review of the differential diagnoses; and a detailed section on various disease entities. Though we have preserved this basic structure, the book is new and innovative in many ways. There are three new section editors and 160 new contributors to the fifth edition. Of the more than 1,000 photos, illustrations, and algorithms, nearly 400 of them are new to this edition. The book's generous use of tables and algorithms help convey the most essential information quickly and clearly.
Keywords: Internal medicine,Nội khoa